(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
The objective is to verify the adequate costing method that contributes to the decision support process in the Military Police of Santa Catarina (PMSC). Thus, the study costing methods that can be used in the public sector. It is a descriptive, documentary, qualitative research and a case study. With the purpose of analyzing the costing systems and focusing on some costing methods, such as standard costing, direct or variable costing, absorption costing and costing by activity (ABC), thus supporting the decision making process of this public agency. Thus, each costing method provides information, as well as its advantages and disadvantages, and allows the calculation of its total and unit costs. In the analysis of the results, it is more appropriate to apply the absorptive costing method, since it identifies the costs of each good or service produced by the organization and is the most cost-effective, that is, little costly in relation to the others and how it is a organization needs to know in detail where the costs come from. As a result of the survey, the difference between the years analyzed by the absorption cost method decreased by two hundred and fifty reais and thirty-three cents from 2014 to 2015; and seventy-four reais and twenty-six cents from 2015 to 2016. Adding a decrease of three hundred and twenty-four reais and fifty-nine cents from the first (2014) to the last year (2016). Analyzing until July 2017, there was a decrease in fifty-six reais and sixty-one cents in 2016 to July / 2017. The appropriate method through the analysis of the results indicated that the absorption costing method is the most suitable for decision making of this public body.